2003
DOI: 10.1042/cs20030184
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and hormonal effects of subcutaneous administration of ghrelin, a novel growth hormone-releasing peptide, in healthy humans

Abstract: Ghrelin is a novel GH (growth hormone)-releasing peptide isolated from the stomach. The cardiovascular and hormonal effects of the subcutaneous administration of ghrelin in humans remain unknown. Six healthy volunteers each received subcutaneous administration of three doses of ghrelin (1, 5 or 10 microg/kg) and placebo; the order of administration was randomized, and separate doses were given at least 24 h apart. The serum GH level dose-dependently increased from 0.5 +/- 0.4 to 3.6 +/- 2.1 ng/ml (1 microg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 18 publications
5
77
0
3
Order By: Relevance
“…The hepatic GH effector IGF-1 levels are not correspondingly increased in conditions with high endogenous plasma ghrelin levels, such as ghrelin-producing tumours (Corbetta et al, 2003;Tsolakis et al, 2004). Furthermore, the administration of ghrelin does not significantly affect the IGF-1 level in healthy volunteers (Enomoto et al, 2003), patients with cardiovascular (Nagaya et al, 2004) or pulmonary diseases (Nagaya et al, 2005), tumour-bearing animals (DeBoer et al, 2007), or our patients with CACS. In contrast, studies using synthetic oral ghrelin mimetics have shown a significant effect on the IGF-1 level in volunteers and in the frail elderly (Smith, 2005) or patients with cancer cachexia (Garcia et al, 2007).…”
Section: Intravenous Ghrelin For Cancer Anorexia/cachexia F Strasser mentioning
confidence: 95%
See 1 more Smart Citation
“…The hepatic GH effector IGF-1 levels are not correspondingly increased in conditions with high endogenous plasma ghrelin levels, such as ghrelin-producing tumours (Corbetta et al, 2003;Tsolakis et al, 2004). Furthermore, the administration of ghrelin does not significantly affect the IGF-1 level in healthy volunteers (Enomoto et al, 2003), patients with cardiovascular (Nagaya et al, 2004) or pulmonary diseases (Nagaya et al, 2005), tumour-bearing animals (DeBoer et al, 2007), or our patients with CACS. In contrast, studies using synthetic oral ghrelin mimetics have shown a significant effect on the IGF-1 level in volunteers and in the frail elderly (Smith, 2005) or patients with cancer cachexia (Garcia et al, 2007).…”
Section: Intravenous Ghrelin For Cancer Anorexia/cachexia F Strasser mentioning
confidence: 95%
“…(Nagaya et al, 2001a;Wren et al, 2001;Akamizu et al, 2004;Schmid et al, 2005;Levin et al, 2006) or subcutaneous (Enomoto et al, 2003;Druce et al, 2006) ghrelin showed safety and tolerability at dosages up to 10 mg kg À1 -sufficient to promote orexigenic, prokinetic, and GH-releasing effects; in those studies, a sensation of warmth, sleepiness, bowel movements, and hunger were reported. Comparable results with i.v.…”
mentioning
confidence: 98%
“…Although ghrelin has been administered subcutaneously to human subjects for evaluation of cardiac effects, the food intake response was not assessed. 8 We performed a double-blind, randomized, crossover trial in order to determine the effect of subcutaneous ghrelin on food intake in man.…”
Section: Introductionmentioning
confidence: 99%
“…IGFBP-1 concentrations were associated with ghrelin concentrations only in subjects with IR. Since ghrelin has a powerful GH-releasing effect in experimental settings [1,8,17,18], it has been proposed to serve as a regulator of somatotroph function together with GHRH and somatostatin [39,40]. However, the physiological role of ghrelin in the regulation of GH/IGF-I axis has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its marked growth hormone (GH)-releasing activity [1], ghrelin acts as a powerful orexigenic hormone [3,4] and this effect appears to be independent of changes in GH [5]. Recent studies have shown that ghrelin also modulates insulin and glucose metabolism [6], and it has further been shown to have beneficial hemodynamic properties [7,8]. It is a somatotrophic, orexigenic and adipogenic hormone, which may link the regulatory systems for growth and energy balance [9].…”
mentioning
confidence: 99%